2020
DOI: 10.3390/pathogens9060450
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset HTLV-1-Associated Myelopathy/Tropical Spastic Paraparesis

Abstract: Background: Vertical transmission of HTLV-1 could lead to the early development of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). This significantly affects quality of life and increases morbimortality. Objective: To describe the epidemiological and clinical characteristics of patients with early-onset HAM/TSP, defined as disease onset before 20 years of age. Methods: This is a retrospective study from an HTLV-1 clinical cohort between 1989 and 2019. We searched for medical records of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…Some factors previously identified are hope, acceptance of pain, and optimism, which have also been observed to affect functionality. However, it has been identified that there is bi-directionality in the interaction between depression and pain, with an increase in its perception in those who are depressed; this would be even more pronounced in patients with a prolonged early-onset disease, which is not rare 2,3 .…”
Section: Dear Editormentioning
confidence: 99%
“…Some factors previously identified are hope, acceptance of pain, and optimism, which have also been observed to affect functionality. However, it has been identified that there is bi-directionality in the interaction between depression and pain, with an increase in its perception in those who are depressed; this would be even more pronounced in patients with a prolonged early-onset disease, which is not rare 2,3 .…”
Section: Dear Editormentioning
confidence: 99%
“…HAM/TSP occurrence is generally associated with infection in adulthood through sexual transmission or blood transfusion. It is important to note that patients with juvenile HAM/TSP have been seen [62,63] and that ATLL is a major cause of death in HAM/TSP patients [64], suggesting that the transmission and pathogenesis of these two classes of HTLV-1 disease may not be entirely unrelated. Prior to onset of symptoms, clinical latency is typically anywhere from a couple of years to decades following infection (reviewed in [65,66]).…”
Section: The Clinical Spectrum Of Htlv-1 Infectionmentioning
confidence: 99%
“…In Peru, HTLV-1 prevalence in candidate blood donors varies from 1.2% to 1.7% across regions, with higher figures for some Andean areas [10]. Most studies have taken place in Lima or the Andes [11][12][13], whereas there are scant data from the Amazon [11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%